Workspace Mapping and Force Control for the 3-DOF Robot - Tien Dat Nguyen,; Phi Cuong Ly,; Minh Khiem Tran,; Duc Thien Tran, (Journal of Technical Education Science, 2024)
This paper proposes a mapping method to unify two workspaces for the robot arm on the teleoperation system and apply the haptic method when the robot enters the singularity area. The teleoperation system mainly consists of a single master and a single slave. The master is a joystick device, and the slave is a 3-DOF manipulator. The master effectuates a setpoint signal to control the 3-DOF manipulator movement along a planned trajectory. Master and slave communicate via a wireless network. Due to differences in structure and dimensions, the workspaces of the master and slave are not analogous. Therefore, the Position mapping method is utilized to map two workspaces together. Otherwise, when the slave moves out of the limited space, the manipulator does not operate. The Haptic feedback is proposed to create the force, which reflects the palm of the operator. So the operator can feel and move to the permitted workspace. Several experiments have been implemented on the actual model to evaluate the effectiveness of the proposed system. The experimental results show the potential use of the teleoperation robotic system employing the Novint Falcon device, 3-DOF manipulator, and Position mapping method. This efficient mapping technique spans the slave workspace with high dexterity.